Investigating the impact of product durability on the economics of remanufacturing. - Zileli, Nejat (2020)
Increasing environmental legislation and growing benefits of circular economies led people to investigate the potential benefits of Closed-Loop Supply Chains (CLSC). Therefore, in recent years, creating value by managing product returns in a CLSC has gained importance. Although much research has been carried out in CLSC with remanufacturing, the research which focusses on the importance of supply-loop constraints was limited. This study aims to discuss the profitability and managerial policies in remanufacturing under limited component durability. During this study, cost comparisons with an open-loop supply chain were made to discuss the feasibility of remanufacturing. The problem is modeled by using a linear programming approach due to its ability to investigate different scenarios in a short amount of time. Morever, a numerical analysis was done to gain managerial insights and to come up with a decision rule that works in stochastic environments. A decision rule has been found. The decision rule was tested against an stochastic scenario by using a simulation technique. The result of this study show under which parameters the CLSC is more profitable than an open-loop supply chain. The decision rule indicates when a manager should hold inventories, make remanufacturing decisions, and decide on when to manufacture new products even under stochastic customer residence times.